Differences in the Mechanical Properties of the Developing Cerebral Cortical Proliferative Zone between Mice and Ferrets at both the Tissue and Single-Cell Levels - Nagasaka, Arata; Shinoda, Tomoyasu; Kawaue, Takumi; Suzuki, Makoto; Nagayama, Kazuaki; Matsumoto, Takeo; Ueno, Naoto; Kawaguchi, Ayano; Miyata, Takaki (Frontiers in Cell and Developmental Biology, 2016)
Cell-producing events in developing tissues are mechanically dynamic throughout the cell cycle. In many epithelial systems, cells are apicobasally tall, with nuclei and somata that adopt different apicobasal positions because nuclei and somata move in a cell cycle–dependent manner. This movement is apical during G2 phase and basal during G1 phase, whereas mitosis occurs at the apical surface. These movements are collectively referred to as interkinetic nuclear migration, and such epithelia are called “pseudostratified”. The embryonic mammalian cerebral cortical neuroepithelium is a good model for highly pseudostratified epithelia, and we previously found differences between mice and ferrets in both horizontal cellular density (greater in ferrets) and nuclear/somal movements (slower during G2 and faster during G1 in ferrets). These differences suggest that neuroepithelial cells alter their nucleokinetic behavior in response to physical factors that they encounter, which may form the basis for evolutionary transitions towards more abundant brain-cell production from mice to ferrets and primates. To address how mouse and ferret neuroepithelia may differ physically in a quantitative manner, we used atomic force microscopy to determine that the vertical stiffness of their apical surface is greater in ferrets (Young’s modulus = 1700 Pa) than in mice (1400 Pa). We systematically analyzed factors underlying the apical-surface stiffness through experiments to pharmacologically inhibit actomyosin or microtubules and to examine recoiling behaviors of the apical surface upon laser ablation and also through electron microscopy to observe adherens junction. We found that although both actomyosin and microtubules are partly responsible for the apical-surface stiffness, the mouse<ferret relationship in the apical-surface stiffness was maintained even in the presence of inhibitors. We also found that the stiffness of single, dissociated neuroepithelial cells is actually greater in mice (720 Pa) than in ferrets (450 Pa). Adherens junction was ultrastructurally comparable between mice and ferrets. These results show that the horizontally denser packing of neuroepithelial cell processes is a major contributor to the increased tissue-level apical stiffness in ferrets, and suggest that tissue-level mechanical properties may be achieved by balancing cellular densification and the physical properties of single cells.